Cell growth inhibition and apoptotic effect of the rexinoid 6-OH-11-O-hydroxyphenantrene on human osteosarcoma and mesenchymal stem cells - Dozza, Barbara; Papi, Alessio; Lucarelli, Enrico; Scotlandi, Katia; Pierini, Michela; Tresca, Giuseppina; Donati, Davide; Orlandi, Marina (Toxicology in vitro, 2012)
► The rexinoid IIF is a synthetic derivative of ATRA with clinical potential. ► IIF is able to induce growth inhibition and apoptosis in different human OS cells and MSC. ► IIF may be an effective compound for anticancer treatment, including that of OS. Natural derivatives of vitamin A, including all-trans-retinoic acid (ATRA), commonly known as retinoids, currently produce favorable results in the treatment of many types of tumors. The rexinoid 6-OH-11-O-hydroxyphenantrene (IIF) is a synthetic derivative of ATRA. Previous in vitro and in vivo studies demonstrated that IIF is able to induce growth inhibition of various cancer cells and is a potent apoptosis-inducing agent with clinical potential. Osteosarcoma (OS) is the most common type of bone cancer, characterized by a rising aggressiveness. Recent evidences suggest that mesenchymal stem cells (MSC) may favour tumor growth and progression. Thus, it is important to investigate whether a compound with potential anti-tumoral properties such as IIF affects not only tumor cells but also MSC. The current study is an attempt to understand the mode of the potential cytotoxicity of IIF on OS cells and MSC. The response to IIF treatment of osteosarcoma SaOS-2, MG63, and U2OS cells and of bone marrow-derived MSC was the subject of investigation. The results showed that IIF significantly inhibited cell growth in OS cell lines and MSC in both a time- and dose-dependent manner, as evaluated by methylene blue assay. This was also associated with altered cell morphology and an increase in cell death with the involvement of apoptosis as demonstrated by NucleoCounter, Hoechst 33342 staining and FACS analysis. No cell death and apoptosis was found in U2OS cells. Analysis of cells treated with 20 and 40μM IIF for 24h by western blot suggests the activation of initiator caspase 9, indicating the involvement of caspases in inducing apoptosis. Furthermore, IIF upregulated the expression of the pro-apoptotic protein Bax and downregulated the anti-apoptotic protein Bcl2. For the first time, our results collectively provide an evidence for cell growth inhibition and activation of apoptosis in human OS cells and MSC by IIF. These results confirm that IIF may be an effective compound for anticancer treatment, including that of OS.